THE EFFECTIVENESS OF ELECTRONIC CLASSES IN THE ACHIEVEMENT OF FIFTH GRADE STUDENTS IN ART EDUCATION - Ammar Abdul Hamid Katran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to identify: The effectiveness of the electronic grades in the achievement of students in the fifth grade of art education Search Hypothesis: There is no statistically significant difference between the mean scores of the experimental group which is taught using the electronic classes and the control group which is taught in the traditional method in art education at the level of (0,05) in the post-cognitive test. The sample of the study was a student of Zulfiqar Primary School of Baghdad Baghdad Education Karkh/ 2 academic year 2016 - 2017 The researcher reached the following results: These classes offer the presentation of the material in an interesting and enjoyable way. Presentation of scientific material sequentially and sequentially and simply. Save time, effort and energy to the teacher. The researcher suggested conducting similar studies in some subjects and using the electronic classes in a broader manner.